Tactile textiles : using textiles as a source of tactile and touch therapy for children who are suffering from tactile sensory dysfunction - Cheong, Tong Pei (2013)
This project aims to use textiles as a form of tactile touch therapy integrated into the current occupational therapy treatments and developed into a range of sensory toys targeted at children who suffer from sensory processing disorders particularly in the tactile sense eg. oversensitive, under responsive to the sense of touch. [2nd Award]